Facile, fast, and inexpensive synthesis of monodisperse amorphous Nickel-Phosphide nanoparticles of predefined size - Mandel, K; Dillon, F; Koos, A; Aslam, Z; Jurkschat, K; Cullen, F; Crossley, A; Bishop, H; Moh, K; Cavelius, C; Arzt, E; Grobert, N (2011)
Monodisperse, size-controlled Ni-P nanoparticles were synthesised in a single step process using triphenyl-phosphane (TPP), oleylamine (OA), and Ni(ii)acetyl-acetonate. The nanoparticles were amorphous, contained ∼30 at% P and their size was controlled between 7-21 nm simply by varying the amount of TPP. They are catalytically active for tailored carbon nanotube growth. © 2011 The Royal Society of Chemistry.